PENERAPAN PENGGUNAAN PROBIOTIK PADA PRODUKSI MASSAL LARVA KERAPU PASIR (Epinephelus corallicola) PADA UNIT PEMBENIHAN BPBAP SITUBONDO - Wiwie Soemarjati; Sugeng Joko Purnomo; Mizab Asdari; Akhmad Romadlon (Faculty of Science and Technology University Ibrahimy, 2016)
The grouper fish hatchery has been growing rapidly include humpback grouper and tiger grouper. On the other hand there are many more types of grouper that has high economic potential, one of which is sand grouper (Epinephelus corallicola). E. corallicola including one type of grouper has a high economic value. Mechanical increased production of grouper culture is by the application of probiotics in aquaculture systems.This study aims to determine the role of probiotics in grouper aquaculture sand. D1-10 larval fish oil given 0.1 ml / m2, probiotic before use cultured using sterile fresh water for 8 hours and then filtered (bottom sediment can not participate), probiotics do when the larvae D1 - harvest with 0.25 -1 ppm and fish health in visual inspection is done every day. These results indicate an increase of the use of probiotics are able to improve the quality and quantity of production of larvae E.corallicola, results can be seen on Survival rate increased by 6.55%.